Promotion of Fruit Consumption Using Nutrition and Health Claims: Sufficiency of Available Data on Nutrition Composition - Anita Kušar; Kerstin Pasch; Igor Pravst (Proceedings)
Fruits constitute a dietary source of many essential nutrients and other bioactive substituents. Unfavorable trends in the consumption of fruits can be addressed with increased promotion and also using nutrition and health claims because an important segment of consumers is sensitive to health-related communications. The regulation on the use of nutrition and health claims only allows the use of claims when the product is a relevant source of the nutrient referred to. Food composition databases (FCDBs) offer such data, but it should be highlighted that, in practice, the composition of fruits can vary notably due to the variety, agricultural practices, soils, and climatic conditions. The objective of the present study was to investigate data on the nutritional composition of selected widely available apple varieties in Europe for health promotion purposes. We focused on samples available to consumers at the end of the season (winter). The comparison of existing data from FCDBs with new nutritional composition data from laboratory analyses for health promotion purposes was performed for four studied apple varieties (Golden Delicious, Gala, Idared, and Braeburn). The amount of vitamin C in the observed samples varied up to 15.3 mg, and the dietary fibres varied from 3.3 to 5.5 g in 100 g of apple in laboratory testing. Only the Braeburn variety contained a sufficient amount of vitamin C for the use of nutrition and health claims, while the content of dietary fibre was sufficient for all varieties. The data from laboratory testing differed from the data from FCDBs, which are not specific to the variety. The findings indicate a moderate acceptability of data on nutritional composition from FCBDs for the use of nutrition and health claims for apples, especially when the content of nutrients is on the borderline of the conditions for the use of claims, as in the case with vitamin C. Consequently, additional research on the variability of vitamin C in apples is needed, especially in relation to the variety and storage conditions/duration. The amendment of FCDBs with composition data at the level of fruit variety would present an important aspect for the nutrition and health promotion of fruits.